(3R, 3'R)-zeaxanthin protects the retina from photo-oxidative damage via modulating the inflammation and visual health molecular markers. (3rd April 2019) - Sahin, Kazim; Akdemir, Fatih; Orhan, Cemal; Tuzcu, Mehmet; Gencoglu, Hasan; Sahin, Nurhan; Ozercan, Ibrahim H.; Ali, Shakir; Yilmaz, Ismet; Juturu, Vijaya
Abstract: Purpose: Zeaxanthin protects the macula from ocular damage due to light or radiation by scavenging harmful reactive oxygen species. In the present study, zeaxanthin product (OmniXan®; OMX), derived from paprika pods (Capsicum annum; Family-Solanaceae), was tested for its efficacy in the rat retina against photooxidation. Methods: Forty-two male 8-week-old Wistar rats exposed to 12L/12D, 16L/8D and 24L/0D hours of intense light conditions were orally administrated either 0 or 100 mg/kg BW of zeaxanthin concentration. Retinal morphology was analyzed by histopathology, and target gene expressions were detected with real-time polymerase chain reaction methods. Results: OMX treatment significantly increased the serum zeaxanthin concentration ( p <  0.001) and ameliorated oxidative damage by increasing the antioxidant enzyme activities in the retina induced by light ( p <  0.001). OMX administration significantly upregulated the expression of genes, including Rhodopsin (Rho), Rod arrestin (SAG), Gα Transducin 1 (GNAT-1), neural cell adhesion molecule (NCAM), growth-associated protein 43 (GAP43), nuclear factor-(erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase (HO-1) and decreased the expression of nuclear factor-κB (NF- κB) and GFAP by OMX treatment rats. The histologic findings confirmed the antioxidant and gene expression data. Conclusions: This study suggests that OMX is a potent substance that can be used to protect photoreceptor cell degeneration in the retina exposed to intense light.